Ghosts! A location-based Bluetooth LE mobile game for museum exploration - Nilsson, Tommy; Blackwell, Alan F.; Hogsden, Carl; Scruton, David (Inter-Disciplinary Press, 2016)
BLE (Bluetooth Low Energy) is a new wireless communication technology that, thanks to reduced power consumption, promises to facilitate communication between computing devices and help us harness their power in environments and contexts previously untouched by information technology. Museums and other facilities housing various cultural content are a particularly interesting area of application. The University of Cambridge Museums consortium has put considerable effort into researching the potential uses of emerging technologies such as BLE to unlock new experiences enriching the way we engage with cultural information. As a part of this research initiative, our ambition has been to examine the challenges and opportunities introduced by the introduction of a BLE-centred system into the museum context. We present an assessment of the potential offered by this technology and of the design approaches that might yield the best results when developing BLE-centred experiences for museum environments. A pivotal part of our project consisted of designing, developing and evaluating a prototype mobile location-based BLE-centred game. A number of technical problems, such as unstable and fluctuating signal strength, were encountered throughout the project lifecycle. Instead of attempting to eliminate such problems, we argued in favour of embracing them and turning them into a cornerstone of the gameplay. Our study suggested that this alternative seamful design approach yields particularly good results when deploying the technology in public environments. The project outcome also demonstrated the potential of BLE-centred solutions to reach out and engage new demographics, especially children, extending their interest in museum visits.